2021
DOI: 10.1002/biof.1814
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin protects swine testis cells from bisphenol A‐induced apoptosis via Keap1/Nrf2 signaling pathway

Abstract: Bisphenol A (BPA) has caused serious pathologies in varying organs of humans and animals, especially reproductive organs. Naringenin (NRG) is a flavanone compound that has shown protective effects against several environmental chemicals through suppression of oxidative stress and activation of nuclear factor erythroid 2-related factor 2 (Nrf2) pathway. Herein, we described the discovery path of NRG inhibition on apoptosis in BPA exposed swine testis (ST) cells through targeting Kelch-like ech-associated protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…BPA, as a typical endocrine disruptor, is one of the most widely used industrial chemicals worldwide, and its threat to human and animal health has long been of concern owing to its adverse impact on both the environment and exposed organisms (Pelch et al, 2019). BPA exposure can induce damage to multiple organs, including the liver (Sun et al, 2021), testis (Chen et al, 2021), and ovary (Biswas et al, 2020), and so forth, among them, the kidney is also a sensitive organ for BPA exposure (Bosch‐Panadero et al, 2018; Priego et al, 2021; Q. Wang, Chen et al, 2020). Se deficiency is a constantly occurring disease that has caused damage to a broad range of tissues and cells (Rayman, 2012), including the liver (Tang et al, 2020), heart (Yang et al, 2021), and vein endothelial cells (Pan et al, 2018), in particular the kidney attributed to it being a target organ for Se deficiency (Iglesias et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BPA, as a typical endocrine disruptor, is one of the most widely used industrial chemicals worldwide, and its threat to human and animal health has long been of concern owing to its adverse impact on both the environment and exposed organisms (Pelch et al, 2019). BPA exposure can induce damage to multiple organs, including the liver (Sun et al, 2021), testis (Chen et al, 2021), and ovary (Biswas et al, 2020), and so forth, among them, the kidney is also a sensitive organ for BPA exposure (Bosch‐Panadero et al, 2018; Priego et al, 2021; Q. Wang, Chen et al, 2020). Se deficiency is a constantly occurring disease that has caused damage to a broad range of tissues and cells (Rayman, 2012), including the liver (Tang et al, 2020), heart (Yang et al, 2021), and vein endothelial cells (Pan et al, 2018), in particular the kidney attributed to it being a target organ for Se deficiency (Iglesias et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, oxidative stress has been a crucial trigger for apoptosis and necroptosis induced by BPA and Se deficiency, for BPA, its exposure could promote oxidative stress and lead to apoptosis in broad range of tissue cells, including human neuroblastoma cells (C. Wang et al, 2021), fish lymphocytes (Q. Liu et al, 2020) and swine testis cells (Chen et al, 2021), and additionally, BPA caused necroptosis in chicken bursa via oxidative stress (L. Liu et al, 2021), for Se deficiency, it could cause apoptosis and necroptosis in swine liver (Y. Zhang et al, 2020) and human uterine smooth muscle cells (Y. Wang, Li et al, 2021) through oxidative stress. Similarly, in the present study, we observed that levels of ROS and MDA in the BPA group and Low‐Se group were obviously induced, and activities of SOD, CAT, and Gpx were markedly reduced (Figure 1 and 4), especially ROS and MDA levels in Low‐Se + BPA group were significantly higher than BPA group and Low‐Se group, and activities of SOD, CAT, and Gpx in Low‐Se + BPA group were remarkably lower than BPA group and Low‐Se group (Figure 1 and 4), suggesting that oxidative stress occurred in both Low‐Se group and BPA group, and Se deficiency exacerbated oxidative stress induced by BPA in the chicken kidney.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DBP (Sigma‐Aldrich, Saint Louis, MO) was dissolved in dimethyl sulfoxide (DMSO) (Solarbio) to prepare a stock solution of 72.0 mM, and then diluted with DMEM to obtain a serial dilution of DBP. According to our previous report, 43 NRG (≥98%, Aladdin, Shanghai, China) was dissolved with DMSO and then diluted with DMEM for a working concentration of 25.39 nM (containing 0.015% v/v DMSO). PTEN, PI3K, AKT, p‐PI3K, p‐AKT, cytochrome C (Cytc), Caspase 3, Caspase 9, B‐cell lymphoma‐2 (Bcl‐2), and Bcl‐2‐Associated X (Bax) polyclonal antibodies were provided by Wanlei (Wanlei, Shenyang, China) or Abmart (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%